Selective Activation of Anticancer Chemotherapy by Cancer-Associated Fibroblasts in the Tumor Microenvironment. (11th September 2016) - Kim, Mi-Gyeong; Shon, Yuna; Kim, Jinyoung; Oh, Yu-Kyoung
Abstract : Background: The tumor microenvironment has recently emerged as a new target of anticancer chemotherapy. Selective activation of anticancer chemotherapy in the tumor microenvironment would further reduce the toxicity of anticancer drugs toward normal tissues. Fibroblast activation protein (FAP) is known to be selectively overexpressed on cancer-associated fibroblasts (CAFs) in the tumor microenvironment. Here, we designed an anticancer chemotherapeutic system based on promelittin, a peptide toxin that is selectively converted from an inactive form to the pore-forming melittin upon cleavage by FAP in the tumor microenvironment. Methods: We conjugated promelittin-containing FAP-cleavable sequences to pegylated phospholipids and anchored them to reduced graphene oxide (rGO) nanosheets. The resulting nanosheets, PL-rGO, were tested for hemolysis and used for doxorubicin delivery. In vitro cocultures and in vivo tumor growth (n = 5 mice per group) with tissue immunostaining were used to test the selective activation of anticancer chemotherapy by FAP expressed on CAFs. Results: FAP-specific hemolytic activity of PL-rGO was observed in cocultures of CAFs and HT29 cells but not in HT29 cells alone. Doxorubicin-loaded PL-rGO (Dox/PL-rGO) showed 3.4-fold greater cell-killing efficacy (compared with free Dox in the CAF/HT29 coculture system, effects that were not observed in HT29 cells alone). Intravenously administered Dox/PL-rGO reduced the growth of HT29 tumors more effectively than other treatments (Dox/PL-rGO: mean = 200.6 mm 3, 95% confidence interval [CI] = 148.7 to 252.5 mm 3 ; free Dox: mean = 697.0 mm 3, 95% CI = 646.9 to 747.1 mm 3, PL: mean = 565.0 mm 3, 95% CI = 550.5 to 579.6 mm 3 ; Dox/rGO: mean = 637.6 mm 3, 95% CI = 619.5 to 655.7 mm 3 ; PL-rGO: mean = 464.4 mm 3, 95% CI = 433.0 to 495.8 mm 3 ). Immunostaining of tumor tissues revealed that survival of CAFs and HT29 cells was lowest in the group treated with Dox/PL-rGO. Conclusions: The demonstration of selective activation of PL-rGO by FAP on CAFs suggests that PL-rGO may serve as a tumor microenvironment–responsive anticancer chemotherapy system.